Essential contribution of habitats in non-protected areas to climate-driven species migration in China - Jie Su; Fanhua Kong; Haiwei Yin; Michael E. Meadows; Liding Chen; Hong S. He; Hui Sun; Zhenya Li; Kejing Zhou; Bin Chen (Geography and Sustainability)
Given the reality of climate-driven migration, the net effectiveness of existing spatially fixed protected areas (PAs) to biodiversity conservation is expected to decline, while the potential of non-PA habitats (non-PAs, i.e., natural, altered, or artificial ecosystems that are not formally designated as PAs) for biodiversity conservation is gaining attention. However, the contribution of non-PAs to biodiversity conservation remains poorly understood. With the aim of comprehensively assessing the effectiveness of non-PAs as transient refugia and steppingstones during future climate-change-induced migration of species in China, a six-metric integrated framework was applied and statistics of these metrics for PAs and non-PAs are compared. Results reveal that, a greater area of non-PAs has a low velocity of climate change (VoCC) compared to that of PAs, and can therefore serve as temporary refugia for species. The disappearing climate index (DCI) and novel climate index (NCI) results show that some 17 % of the subdivided climate classes within the PAs have changed. However, the displacement index (DI) results imply that nearly half (48.98 %) of the PAs need non-PAs to provide transient refugia for climate-driven migration of species in PAs. The higher ratio of effective steppingstones measured using the climate corridor score (CCS) and landscape current flow (LCF) further emphasizes that non-PAs play a more significant role as steppingstones for climate-driven migration than do PAs in terms of both their structural and functional connectivity. Our research further demonstrates that a conservation approach that improves connectivity among PAs and considers Other Effective area-based Conservation Measures (OECMs) is essential for long-term biodiversity adaptation to climate change.